Protokol Keluar dan Masuk Rumah Selama Pandemi Covid-19 - Raja Fitrina Lestari; Lita Lita (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2021)
The spread of COVID-19 in Indonesia has significantly increased and become widespread throughout various areas and countries along with the spike of the number of cases and/or the number of deaths. Therefore, it needs accelerated handling in the form of Large-scale social restrictions (Indonesian: Pembatasan Sosial Berskala Besar or PSBB) in order to curb the spread of COVID-19. The aim of this outreach program is make videos on protocol to leave and enter the house during the COVID-19 pandemic. The method used is to make the videos and then spread them to the community via social media. The aim of this activity is to provide useful information via social media, which is Youtube channel, about the protocol to leave and enter the house during COVID-19 pandemic. The result shows that there are advantages provided to the viewers, and the videos gained 28 likes, 65 subscribers, and have been watched 71 times. Regarding health protocol compliance, it is also hoped to provide assistance program for community by monitoring and reminding them to apply health protocol when both entering and leaving their houses amid the pandemic, and also by intensifying 3M campaign ( maintaining distance, washing hands, wearing masks) as well as 3T campaign (tracing, treatment, testing). Both are equally important to be well implemented in order to curb the spread of COVID-19